Communication theory & research an EJC anthology - McQuail, Denis; Golding, Peter, 1947-; Bens, Els de. (London : SAGE, 2005)
This collection of papers represents some of the finest communications research published over the last decade. 21 papers have been selected, all of which make significant and valuable interventions in the field of media and communications.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Communication